Integrating platelet and coagulation activation in fibrin clot formation. Issue 3 (20th May 2018) - Swieringa, Frauke; Spronk, Henri M.H.; Heemskerk, Johan W.M.; van der Meijden, Paola E.J.
Abstract: Platelets interact with the coagulation system in a multitude of ways, not only during the phases of thrombus formation, but also in specific areas within a formed thrombus. This review discusses current concepts of platelet control of thrombin generation, fibrin formation and structure, and anticoagulation. Indicated are how combined signalling via the platelet receptors for collagen (glycoprotein VI) and thrombin induces the secretion of (anti)coagulation factors, as well as surface exposure of phosphatidylserine, thereby catalysing thrombin generation. This procoagulant platelet response is also facilitated by the adhesive complexes glycoprotein Ib‐V‐IX and integrin αIIb β3 . In the buildup of a platelet‐fibrin thrombus, the extrinsic, tissue factor–driven coagulation pathway is predominant in early stages, while the intrinsic, factor XII pathway seems to promote at later time points. Already early generation of thrombin enforces platelet responses and stimulates intra‐thrombus heterogeneity with patches of loosely aggregated, contracted, and phosphatidylserine‐exposing platelets. Fibrin actively formed on the surface of activated platelets supports thrombus growth, but also captures thrombin. The fibrin distribution in a thrombus appears to rely on the local procoagulant trigger and the blood flow rate. Clinical studies support the importance of the platelet‐coagulation interplay, by showing beneficial effects of combination therapy in the secondary prevention of cardiovascular disease.